Highlights from the 2013 WIN Symposium: personalised cancer therapy from innovation to implementation - Schilsky, Richard L (Cancer Intelligence, 2013)
The Worldwide Innovative Networking (WIN) consortium is a global alliance of academic and industrial cancer researchers, clinicians, and cancer advocacy groups set up to promote innovations in personalised cancer therapy and to accelerate the translation of research in this discipline into the oncology clinic. One of its most important initiatives is the WIN symposia, which have been held in Paris each summer since 2009. The fifth WIN symposium, which was held 10–12 July 2013, took as its overall theme ‘Personalised Cancer Therapy: From Innovation to Implementation’. Over 400 delegates, including a good number of representatives of patient groups as well as leading academic, industrial, and clinical scientists; students; and post-docs attended this symposium. Its scientific programme featured thirty presentations divided into four main plenary sessions, and there was also a wide-ranging poster session that encompassed all the topics covered in the plenaries. The programme structure followed the path of drug discovery, in that the first session covered assay development for personalised cancer medicine; the second, applications of genomics in oncology; the third, clinical development; and the fourth, the impact of personalised medicine on cancer care.